2009
DOI: 10.1111/j.1365-3156.2009.02336.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographical distribution and epidemiological features of Old World cutaneous leishmaniasis foci, based on the isoenzyme analysis of 1048 strains

Abstract: SummaryA series of 1048 Leishmania strains from Old World cutaneous leishmaniasis foci, isolated between 1981 and 2005, were studied by isoenzyme analysis. The strains were obtained from humans, rodents, dogs and sandflies from 33 countries. The four typically dermotropic species, Leishmania major, L. tropica, L. aethiopica and L. killicki, were found. The viscerotropic species L. donovani and L. infantum, which can occasionally be responsible for cutaneous leishmaniasis, are not considered in this paper. Leis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
114
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(123 citation statements)
references
References 39 publications
6
114
0
3
Order By: Relevance
“…Thus, other Leishmania species may exist in Mali, but they seem to be rarely observed in the geographic areas where L. major was found. Along with three previous reports confirming the presence of L. major in Mali, [7][8][9] this study suggests that L. major is likely the sole species responsible for CL in Mali and that it is found throughout the country.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Thus, other Leishmania species may exist in Mali, but they seem to be rarely observed in the geographic areas where L. major was found. Along with three previous reports confirming the presence of L. major in Mali, [7][8][9] this study suggests that L. major is likely the sole species responsible for CL in Mali and that it is found throughout the country.…”
mentioning
confidence: 66%
“…7,8 A more recent study identified four different L. major strains in Mali. 9 Although these reports established the presence of L. major in the country, the frequency of specific etiologic agents and the extent of their geographical distribution in Mali remain unknown. In this study, we used Leishmania species-specific polymerase chain reaction (PCR) to confirm the presence and distribution of L. major and determine if other Leishmania species exist or are clinically relevant in Mali.…”
mentioning
confidence: 99%
“…Consequently, most methods can distinguish them. L. killicki, on the other hand, behaves more like a local L. tropica variant and is better not regarded as a separate species (56)(57)(58)(59) (Fig. 2).…”
Section: Clinically Relevant Taxa: Certainties and Doubtsmentioning
confidence: 99%
“…In this complex of four clusters, cluster A (including L. killicki parasites) is the most distant from the others. 2 Since its first description, there has been no epidemiologic investigation of the CL focus in Tataouine. 1 Only sporadic isoenzyme typing of Leishmania strains from patients in this region was conducted.…”
Section: Introductionmentioning
confidence: 99%